Hodograph method in MHD orthogonal fluid flows - P. V. Nguyen; O. P. Chandna (International Journal of Mathematics and Mathematical Sciences)
Equations for steady plane MHD orthogonal flows of a viscous incompressible fluid of finite electrical conductivity are recast in the hodograph plane by using the Legendre transform function of the streamfunction. Three examples are studied to illustrate the developed theory. Solutions and geometries for these examples are determined.